2010
DOI: 10.1073/pnas.1004982107
|View full text |Cite
|
Sign up to set email alerts
|

A pro-resolution mediator, prostaglandin D 2 , is specifically up-regulated in individuals in long-term remission from ulcerative colitis

Abstract: Patients with ulcerative colitis (UC) experience unpredictable bouts of active inflammation and ulceration. Relatively little attention has been paid to the role of antiinflammatory mediators in the pathogenesis of UC, although rodent studies suggest an important role of prostaglandin (PG) D 2 in the resolution of tissue injury and inflammation. The present study was performed to determine if colonic PGD 2 synthesis was altered in patients in remission from UC and if expression of the key enzymes and receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 31 publications
3
58
0
2
Order By: Relevance
“…Several studies have demonstrated that PGE 2 , the most abundant and prominent prostanoid in inflammation initiation, is involved in the processes leading to the classical signs of inflammation (36,37). In contrast, PGD 2 par- ticipates in the control of resolution with its prolonged elevation during the later phase of inflammation (13,38,39). Consistent with these reports, our study clearly showed that, in both ex vitro and in vivo experiments, COX-2 was activated throughout the inflammatory response period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have demonstrated that PGE 2 , the most abundant and prominent prostanoid in inflammation initiation, is involved in the processes leading to the classical signs of inflammation (36,37). In contrast, PGD 2 par- ticipates in the control of resolution with its prolonged elevation during the later phase of inflammation (13,38,39). Consistent with these reports, our study clearly showed that, in both ex vitro and in vivo experiments, COX-2 was activated throughout the inflammatory response period.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to its well-known role as a pharmaceutical target for anti-inflammatory drugs in inflammatory diseases, COX-2 also exerts versatile biological activities to resolve inflammation (7)(8)(9). At the onset of inflammation, COX-2 has a potent proinflammatory effect, predominantly through the generation of PGE 2 , whereas in the resolution phase, COX-2 is responsible for producing proresolving PGs, such as PGD 2 , 15-deoxy-D 12,14 -PGJ 2 , and PGF 2a (10)(11)(12)(13). Notably, PGE 2 and PGD 2 are responsible for modulating lipid mediator class switching from proinflammation to proresolution, as they have been shown to initiate the production of 15-lipoxygenase, a pivotal enzyme that is capable of mediating the biosynthesis of proresolving lipid mediators (14).…”
mentioning
confidence: 99%
“…Furthermore, these individuals would be expected to be deficient in a number of COX-2 products, such as prostaglandin D 2 39 and 15-deoxy-Δ12 14-prostaglandin J 2 40—as well as the lipoxygenase-produced lipoxins41—which have key anti-inflammatory and pro-resolution roles. Prostaglandin D 2 , for example, has been shown to be specifically upregulated in the long-term remission of ulcerative colitis,42 illustrating a gastrointestinal-protective effect, which would presumably be lacking in these individuals. In this way, mucosal injury can initiate a vicious cycle of ulceration and fibrosis as the lesions persist in the presence of impaired resolution.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, une surexpression de DP1 associée à une augmentation de la production de PGD2 est observée chez les patients en rémission par rapport aux patients en phase active de la maladie [6]. À l'inverse, un effet délétère de la PGD2 a été évoqué dans un modèle de colite induite par instillation d'acide trinitrobenzène sulphonique [22].…”
Section: Synthèse Revuesunclassified
“…Néanmoins, son rôle dans le contrôle de l'homéostasie de la barrière épithéliale intestinale n'est que partiellement élucidé. Les données de la littérature suggèrent qu'au cours des maladies inflammatoires chroniques de l'intestin, la production de PGD2 est plus tardive que celle de PGE2, mais qu'elle serait persistante et contemporaine de la résolution de certains processus inflammatoires [5][6][7]. Deux études récentes portant sur des patients atteints de rectocolite hémorragique montrent l'implication de ce médiateur lipidique dans la physiopathologie de ces maladies inflammatoires [6,8].…”
unclassified